Implementation of an Integrated Accounting System to Reduce Inventory Write-Off Loss Costs: Case Study of PT Terminal Petikemas Surabaya - Bagus Angan Brasilio; Driana Leniwati; Nazaruddin Malik (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Advances in information technology have prompted companies to adopt integrated systems to improve the efficiency and accuracy of inventory management, particularly in reducing inventory write-off costs. This study aims to analyze the implementation of an integrated accounting system based on System Application and Product in Data Processing (SAP) and to identify the challenges and opportunities associated with its implementation at PT Terminal Petikemas Surabaya. An interpretive approach based on a case study was employed, utilizing data collection techniques such as observation, in- depth interviews, documentation, and literature review. The research findings indicate that data integration, real-time processing, and automated controls improve recording accuracy, data consistency with physical conditions, and the efficiency of inventory management. These conditions lead to a reduction in inventory write-off costs through improvements in control processes and inventory planning. Thus, an integrated accounting system plays a strategic role in enhancing the effectiveness of inventory management and the company’s operational efficiency.